Une prison modèle ? La prison circulaire d’Autun, un projet idéal à l’épreuve de la réalité - Agathe Mathiaut-Legros (In Situ)
The circular prison of Autun, designed in 1847 by the architect André Berthier, is a unique example of a panoptic prison that adopted the circular plan in France. Recognised as a national historic monument in 2017, it is now part of a museum project that will lead just as much to its rediscovery as to change its uses. The launch of architectural studies in 2020 has encouraged us to return to this project, in line with the spirit of its time, trying to understand its successes and weaknesses, both architecturally and functionally, and to explore some of the modifications it has undergone.This prison is both a faithful and original translation of the concepts that prevailed when it was designed in the 1840s, advocating individual confinement and largely based on the idea of the panoptic prison developed by J. Bentham. The rigorous translation of these ideas into its architectural form, however, hindered its capacity to adapt to new measures, while weaknesses were quickly identified in the building. In the first decades after its opening in 1856, it was the subject of various redevelopment projects which in turn expressed the new concerns and corrective measures deemed necessary in this prison, which seems never to have functioned perfectly as its designer had intended.